Penerapan Augmented Reality Sebagai Media Pembelajaran Pengenalan Buah-Buahan Beserta Manfaatnya Berbasis Android Dengan Metode Multimedia Development Life Cycle (MDLC) Untuk Anak Usia 7-10 Tahun (Studi Kasus: Perumahan RT 03 Pamulang Barat) - Winni Maeylani; Yolen Perdana Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Information and communication technology is currently developing very rapidly and affects various media that previously existed. The development of information and communication technology involves the multimedia field because it is very effective in conveying information. One of the emerging technologies in the multimedia field is Augmented Reality. Augmented Reality is a technology that is applied to Android mobile device applications because the system in Augmented Reality analyzes objects captured by the camera in real time. With the development of technology, children's interest in learning also tends to decrease, and children are more familiar with technology, such as the daily use of cellphones, which are used to play games or watch YouTube, which has the effect of making children addicted. to learn knowledge or reading decreased interest. One of them is learning about various fruits and their benefits that are less attractive to children, and learning media introduces daily fruits and their benefits, namely according to books or posters that can make it difficult for children to know the benefits. in fruit. However, with the development of technology, children are more interested in the world of technology. With that, the author is interested in making an Augmented Reality application as a learning medium for the introduction of fruits and their benefits based on Android with the Multimedia Development Life Cycle method for children aged 7-10 years, so that they can increase children's knowledge in recognizing fruit and its benefits.